Respostas
respondido por:
2
Olá Gustavo,
Como vai?
Vamos lá:
a)
f(x) = -6x
-6x = 0
x = 0
f(x) = -6 * 0
f(x) = 0
b)
f(x) = -2x + 5
-2x + 5= 0
x = -5 / -2
x = 2,5
f(x) = -2 * 0 + 5
f(x) = 5
c)
f(x) = 3x - 8
3x - 8 = 0
x = 8 / 3
f(x) = 3 * 0 - 8
f(x) = -8
gráficos anexos logo abaixo↓↓↓
Espero ter ajudado (:
Como vai?
Vamos lá:
a)
f(x) = -6x
-6x = 0
x = 0
f(x) = -6 * 0
f(x) = 0
b)
f(x) = -2x + 5
-2x + 5= 0
x = -5 / -2
x = 2,5
f(x) = -2 * 0 + 5
f(x) = 5
c)
f(x) = 3x - 8
3x - 8 = 0
x = 8 / 3
f(x) = 3 * 0 - 8
f(x) = -8
gráficos anexos logo abaixo↓↓↓
Espero ter ajudado (:
Anexos:
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás